Complexation of Eu3+ with a polycarboxylate based concrete superplasticizer in chloride media - Sema Özyagan; Raoul E. Gillmeister; Thomas Sittel; Andrej Skerencak-Frech; Petra J. Panak (Results in Chemistry)
In this work, we present a complexation study of Eu3+ with a commercial polycarboxylate based concrete superplasticizer Glenium® 51 in NaCl media at low to medium ionic strengths. The complexation is investigated using time-resolved laser fluorescence spectroscopy (TRLFS) at pHm = 5.1 ± 0.1. With the charge neutralization model, conditional stability constants log K'm were determined for ionic strengths up to Im (NaCl) = 2.47 mol kg−1 H2O−1. Eu3+ only forms one complex with this complexant under these conditions. The conditional stability constants decrease significantly at elevated ionic strengths by almost three orders of magnitude. Thus, the Eu3+-Glenium® 51 complex formation is reduced at high ionic strengths. The determination of the conditional stability constants allows to extrapolate to the stability constant at zero ionic strength by using the specific ion interaction theory (SIT). A logKm0 = 8.54 ± 0.9 has been determined, which highlights the strong complexation properties of the superplasticizer. Moreover, this novel study presents first insights into the interaction of Glenium® 51 with Eu3+ at various ionic strengths. Since Eu3+ is used as a surrogate for trivalent actinides, these results are very important for understanding actinide behavior in cementitious systems present at the geotechnical barrier of a repository in clay rock formations of Northern Germany containing pore and formation waters with elevated ionic strength.